Use of E-exams in High Stakes Law School Examinations: Student and Staff Reactions - Alex Steel; Lyria Bennett Moses; Julian Laurens; Charlotte Brady (Legal Education Review)
Australian law schools have just begun to move towards e-exams. There are a number of drivers encouraging Australian universities to introduce e-exams, including economic pressures, a desire to reduce administrative burdens, and changes to workplaces. Logistically, e-exams may assist with paper distribution, script legibility and shorter marking times.